2010
DOI: 10.1007/s11881-010-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the phonological processing in French dyslexic children: evidence for the phonological syllable and linguistic features' role in silent reading and speech discrimination

Abstract: This study investigated the status of phonological representations in French dyslexic children (DY) compared with reading level- (RL) and chronological age-matched (CA) controls. We focused on the syllable's role and on the impact of French linguistic features. In Experiment 1, we assessed oral discrimination abilities of pairs of syllables that varied as a function of voicing, mode or place of articulation, or syllable structure. Results suggest that DY children underperform controls with a 'speed-accuracy' d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
(93 reference statements)
1
15
0
2
Order By: Relevance
“…In contrast to spelling research, there is a considerable body of studies that have investigated reading in students with dyslexia (e.g. Bosse & Valdois, ; Casalis, ; Colé & Sprenger‐Charolles, ; de Jong & van der Leij, ; Demont, ; Goswami, ; Griffiths & Snowling, ; Larkin & Snowling, ; Maïonchi‐Pino, Magnan, & Ecalle, ; Manis, Custodio, & Szeszulski, ; Marinus & de Jong, ; Snowling, Goulandris, & Defty, ; Sprenger‐Charolles & Serniclaes, ; Sprenger‐Charolles et al, ; Ziegler & Goswami, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to spelling research, there is a considerable body of studies that have investigated reading in students with dyslexia (e.g. Bosse & Valdois, ; Casalis, ; Colé & Sprenger‐Charolles, ; de Jong & van der Leij, ; Demont, ; Goswami, ; Griffiths & Snowling, ; Larkin & Snowling, ; Maïonchi‐Pino, Magnan, & Ecalle, ; Manis, Custodio, & Szeszulski, ; Marinus & de Jong, ; Snowling, Goulandris, & Defty, ; Sprenger‐Charolles & Serniclaes, ; Sprenger‐Charolles et al, ; Ziegler & Goswami, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that beginning readers rely on the phonological, orthographic, and statistical properties of syllables to process printed words (e.g., Chetail & Mathey, 2009;Colé, Magnan, & Grainger, 1999;Maïonchi-Pino et al, 2010a, 2010b. However, the acoustic-phonetic properties of phonemes within syllabic boundaries have received little attention.…”
mentioning
confidence: 99%
“…De manière générale, nos résultats vont dans le sens desétudes où lesélèves en difficulté ontété comparésà deś elèves du mêmeâge (par ex. : Colin et al, 2007;Griffiths & Snowling, 2001;Maïonchi-Pino et al, 2010). En effet, lesélèves dyslexiques et lesélèves sourds ont des performances plus faibles que leurs pairs du mêmeâge, soit en termes de réussite, de temps de réponse ou les deuxà la fois.…”
Section: Discussion -Experimentationunclassified
“…D'autres chercheurs se sont intéressés aux unités phonologiques plus grandes que le phonème, la syllabe par exemple. Une seconde série d'études plaident en faveur de la syllabe comme unité de lecture et ont montré que les procédures graphosyllabiques sont liées, dans certaineś etudes, aux habiletés en lecture (Colé, Magnan, & Grainger, 1999;Doignon & Zagar, 2006;Duncan & Seymour, 2003;Ferrand, Segui, & Grainger, 1996;Maïonchi-Pino, Magnan, &Écalle, 2010;Prinzmetal, Hoffman, & Vest, 1991;Prinzmetal, Treiman, & Rho, 1986;Sprenger-Charolles & Siegel, 1997;Taft & Radeau, 1995). Ayant eu recoursà divers protocoles méthodologiques, cesétudes ont montré, entre autres, qu'il est plus facile de lire un mot formé de moins de syllabes qu'un mot de plus de syllabes, le nombre de lettreś etantégal, ou qu'il est plus facile d'identifier la couleur d'une lettre lorsque la lettre est de la même couleur que les autres lettres de la syllabe.…”
Section: Introductionunclassified